Основні підходи використання технології на основі кількох входів та кількох виходів - Костень, Т. Б. (ХНУРЕ, 2023)
Information protection in all spheres of activity is becoming more relevant now. The growth of users and the volume of processed information within the information field, which must be protected, has significantly increased. One of the technologies that allows you to solve the problem of capturing large amounts of information without losing bandwidth in the network is a technology with multiple inputs and multiple outputs Multiple Input Multiple Output (MIMO). MIMO is a method of spatial signal coding that allows to increase the bandwidth of the channel, in which the transmitting side uses two or more antennas and the same number of antennas for the receiving side.